Improvement of organizational and methodological issues of analytical control of natural gas quality in Testing laboratory - A. F. Battalov; R. T. Saetova; Ya. V. Denisova (Омский научный вестник)
The increased requirements for the quality of natural gas transported and used in industrial and domestic purposes have significantly increased the role of the analytical laboratory in the production process, since if the results of analyzes that determine the quality of products depend on the entire work of the gas transportation company as a whole, then the quality and reliability of the analysis results themselves are determined by the work of the testing laboratory. The basis of consumer confidence in the purchased products is ensured by the reliability of confirmation of the conformity of products established in the requirements of technical regulations and standards. Confirmation of the quality of products constantly requires the analytical laboratory to implement methods and techniques for monitoring the quality of analyzes. The research base is Gazprom Transgaz Kazan LLC, one of the gas transmission subsidiaries of Gazprom PJSC serving the Uzhgorod and Novopskov gas trunkline corridors, the Nizhnyaya Tura–Perm–Gorky 1,2 gas pipelines, Orenburg–Zainsk, Kazan–Nizhny Novgorod, etc. The object of the study is the analytical control of the quality of natural gas, the subject is organizational and methodological issues for its implementation. This article proposes a method for calculating the frequency of gas sampling using automated algorithms taking into account data on changes in the composition and properties of gas streams for the reporting period. The description of the method is presented on the example of calculating the frequency of determining the calorific value of the lowest (actual calorific value) and density of natural gas. The central chemical-analytical laboratory of the Gazprom Transgaz Kazan’s engineering and technical center and the points of gas sampling at the gas distribution stations of the main gas pipelines in the service area of the сompany are used as objects of the method implementation.